AI in History Education. The American Historical Association’s Guidelines, the Views of Their Authors, and Their Reception within the Historical Community - Ruchniewicz, Krzysztof (Sensus Historiae, 2026)
The article analyses the American Historical Association (AHA) guidelines on the use of artificial intelligence in history education, published in July 2025 - the first document of this kind issued by a major professional association. It consists of three parts. The first examines the document itself: its origins, structure, and five groups of principles, with particular attention to historical thinking, the limitations of generative tools, the concept of AI literacy, and the value of historical expertise. The second part analyses an AHA webinar in which the guidelines’ authors presented five different pedagogical strategies towards AI: cautious incrementalism, radical acceptance, detached analysis, pragmatism under resource constraints, and daily struggle. The third part reconstructs the reception of the document within the historical community, discussing responses from bloggers, columnists, and academic researchers. The article identifies gaps in the guidelines - the omission of the student perspective, visual history, and public history - and raises the question of whether similar standards could and should be developed in the Polish context.